THE PROVISION OF NUTRIENTS AND AUTOMATIC WATERING PLANT BASED ON REAL TIME CLOCK AND SOIL HUMIDITY BASED MICROCONTROLLER ATMEGA32 - Abdullah Abdullah; Masthura Masthura (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2018)
The provision of nutrients and watering plants system is very useful for agriculture as farming support. This system does not only process the watering of plants but already equipped with the provision of nutrients that are needed for the development of plants, so the problem of dry soil conditions and the provision of nutrients that are late (not in time) often causes crop failure is no longer a problem in farming. This research uses a type of soil moisture sensor that has two plates as a sensitivity to readings of electric charge, the DS1307 type of Real Time Clock module which is used as a timer to be read in real time, Atmega32 type of microcontroller that functions as a center for processing all data (input / output), and equipped with a 4 x 20 LCD so that the description of the system both the results of measurements, the time of setting the nutrition and other information can be seen clearly on the LCD screen. From the results of testing obtained to prove that this system has been successfully integrated and able to work properly according to the desired target, which can provide nutrients to plants according to the time set and can do the process of watering plants automatically according to the condition of the soil.Keywords: automatic, soil moisture sensor, nutrition, watering, real time clock